Case Report: Clinical benefit from multi-target tyrosine kinase inhibitor and PARP inhibitor in a patient with cancer of unknown primary with BRCA1 large genomic rearrangement - Yu, Ling; Lin, Jietao; Li, Hanhan; Sun, Lingling; Wang, Shubo; Chen, Yaoxu; Chen, Hanrui; Lin, Lizhu (Frontiers in Pharmacology, 2023)
Background Cancer of unknown primary (CUP) which accounts for 3% to 5% new cancer cases every year is a type of histologically confirmed metastatic tumors whose primary site can’t be confirmed by conventional diagnostic method. For CUP patients, the difficulty in finding the primary site makes them fail to receive more precise therapy. Most patients were treated with empiric chemotherapy with median survival of 6 mouths and even worse prognosis in unfavorite subset of CUP. Case report An 80-year-old woman was presented with masses in abdomen. After comprehensive examinations by imageological and immunohistochemical examination, she was diagnosed with CUP. She strongly refused chemotherapy, thus since July 02, 2019, Anlotinib was administrated with patient consent and stable disease (SD) was observed for 2 years. During subsequent treatment, BRCA1 Large genomic rearrangement was identified in the patient by NGS, and she was observed SD for 6 months after Olaparib treatment. The type of LGR identified in this patient found out to be BRCA1 exon 17-18 inversion (inv), which was never reported before. Conclusion For CUP patients, chemo-free regimen seems acceptable at first-line treatment and NGS-guided targeted treatment could improves participant's outcome.